Three-dimensional analysis of selected kinetics and impulse variables between middle and wing volleyball attackers during block jump based on integration method - Fatahi, A.; Yousefian Molla, R.; Ameli, M. (Journal of Advanced Sport Technology, 2020)
Within the volleyball game skills, Block and Attack are presenting the highest correlation with success, independent of the game phase. Monitoring block jump actions in middle and wing attackers are crucial to improve performance and avoid injuries during this skill, therefore the aim of this study was to investigate the 3-Dimensional analysis of selected kinetics and impulse variables between middle and wing volleyball attackers during block jump based on integration method. 21 healthy junior volleyball players of the national team (11 wing attackers and 10 middle attackers) were selected to participate in this study. The athletic task was Block Jump, performed by middle and wing volleyball attackers. The 3-Dimentional average, maximum and minimum of GRF (Average Force (X, Y, Z), Maximum Force (X, Y, Z), and Minimum Force (X, Y, Z)) were obtained from Force plate system output directly and 3-Dimentional impulse (X, Y, Z) were calculated by integrating force with respect to time. Also, time between two minimum and maximum GRF`s peaks (Time between Two Peaks) were calculated for each jump. Average Mean and Standard Deviation were used for descriptive analysis. Shapiro-Wilk test was used for the normality of data. If so, an Independent t-test was performed to compare any differences of variables in three-dimension between two attackers` groups during block jump. The results highlight that middle attackers have greater average force in Anteroposterior (X) and vertical (Z) directions during block jumps, but wing attackers show larger impulse in vertical (Z) direction as well as greater time duration between minimum and maximum force peaks (p<0.05). These specific differences in variables of two groups may be useful for physical trainers coaches and specialists who will be able to manage task constrains to design proper training programs for optimal performance and minimizing related injuries.